One-dimensional charged kaon femtoscopy in p-Pb collisions at √ˢɴɴ = 5.02 TeV - Acharya, S.; Adamovã, D.; Adhya, S.P.; Adler, A.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; et al. (American Physical Society, 2019)
The correlations of identical charged kaons were measured in p-Pb collisions at √ˢɴɴ = 5.02 TeV by the ALICE experiment at the LHC. The femtoscopic invariant radii and correlation strengths were extracted from one-dimensional kaon correlation functions and were compared with those obtained in pp and Pb-Pb collisions at √s = 7 TeV and √ˢɴɴ = 2.76 TeV, respectively. The presented results also complement the identical-pion femtoscopic data published by the ALICE collaboration. The extracted radii increase with increasing chargedparticle multiplicity and decrease with increasing pair transverse momentum. At comparable multiplicities, the radii measured in p-Pb collisions are found to be close to those observed in pp collisions. The obtained femtoscopic parameters are reproduced by the EPOS 3 hadronic interaction model and disfavor models with large initial size or strong collective expansion at low multiplicities.
Keywords: Physics; Hadron; Particle physics; Large Hadron Collider; Pion; Multiplicity (mathematics); Charged particle; Nuclear physics; Invariant (physics); Ion; Mathematical physics; Geometry; Quantum mechanics; Mathematics; https://purl.org/pe-repo/ocde/ford#1.03.03